1995
DOI: 10.1111/j.1476-5381.1995.tb16668.x
|View full text |Cite
|
Sign up to set email alerts
|

Effects of nicorandil on the recovery of reflex potentials after spinal cord ischaemia in cats

Abstract: 1 The pathophysiological significance of ATP-sensitive K+ (KATP) channels in the central nervous system is not fully understood. In this study the effects of nicorandil (a hybrid vasodilator having a dual mechanism of action as a K+ channel opener and a nitrate) on the recovery of the spinal cord reflex potentials after spinal cord ischaemia were examined and compared with those of pinacidil and nitroprusside in anaesthetized spinal cats. 2 Spinal cord ischaemia was produced by occlusion of the thoracic aorta … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
9
0

Year Published

1997
1997
2016
2016

Publication Types

Select...
4
3

Relationship

2
5

Authors

Journals

citations
Cited by 12 publications
(9 citation statements)
references
References 37 publications
(38 reference statements)
0
9
0
Order By: Relevance
“…Recently we have found that nicorandil and pinacidil, K + channel openers, accelerate the recovery of reflex potentials after a transient spinal cord ischemia in anesthetized spinal cats (Suzuki et al 1995). In contrast, nitroprusside, a NO donor, retarded the recovery of reflex potentials (Suzuki et al 1995).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Recently we have found that nicorandil and pinacidil, K + channel openers, accelerate the recovery of reflex potentials after a transient spinal cord ischemia in anesthetized spinal cats (Suzuki et al 1995). In contrast, nitroprusside, a NO donor, retarded the recovery of reflex potentials (Suzuki et al 1995).…”
Section: Discussionmentioning
confidence: 99%
“…In contrast, nitroprusside, a NO donor, retarded the recovery of reflex potentials (Suzuki et al 1995). These findings prompted us to evaluate the pathophysiological role of NO in the functional recovery after spinal cord ischemia.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Wind et al 32 found protection of cultured neurons against chemically induced hypoxia by bimakalim, a K ATP activator. Suzuki and coworkers 33 showed that pretreatment with pinacidil, a partial K ATP agonist, shortened the recovery time of spinal reflexes after spinal ischemia in cats. When glibenclamide, an inhibitor of K ATP , was coadministered, the protective effect was absent.…”
Section: Discussionmentioning
confidence: 99%
“…The accelerated recovery of polysynaptic reflex potentials elicited by L-NMMA was abolished by coadministration of L-, but not D-arginine. Nitroprusside, an NO donor, retards the recovery of polysynaptic reflex potentials after transient spinal cord ischaemia (Suzuki et al 1995;Nemoto et al 1997). However, it is not known whether inhibition of NOS also improves neurological function in the chronic phase after spinal cord injury.…”
Section: Introductionmentioning
confidence: 99%